Tuta Sindina: The Way Forward in Managing Academia at Escuela Superior Politenica De Chimborazo - Vanegas-Peralta, Pablo; Cordova-Uvidia, Rafael (Journal of Sustainability Perspectives, 2025)
This paper addresses the acute, interconnected socio-ecological challenges facing the Chimborazo province of Ecuador, a region characterized by high rates of poverty, chronic child malnutrition, and severe environmental degradation. These challenges demand a systemic, university-led response that transcends traditional models of outreach and knowledge transfer. The institutional model proposed herein was developed using a Participatory Action Research (PAR) methodology, which integrates a Quintuple Helix framework to engage stakeholders from academia, industry, government, civil society, and the natural environment. The primary result is the Tuta Sindina ecosystem, a novel organizational model for the Escuela Superior Politécnica de Chimborazo (ESPOCH) designed to foster a regional socio-ecological transition. Key features of this model include the creation of interdisciplinary research institutes targeting regional crises, comprehensive curriculum reform based on the principles of Education for Sustainable Development (ESD), and the deep integration of ancestral Kichwa knowledge, particularly the philosophy of Sumak Kawsay (Good Living). This paper concludes that the Tuta Sindina model offers a robust and potentially replicable framework for universities, particularly in the Global South, to function as anchor institutions for regional sustainability, thereby contributing a unique perspective to the global discourse on the role of higher education in achieving the Sustainable Development Goals.